Roles of Krüppel Homolog 1 and Broad-Complex in the Development of Dendroctonus armandi (Coleoptera: Scolytinae) - Sun, Ya-Ya; Fu, Dan-Yang; Liu, Bin; Wang, Lin-Jun; Chen, Hui (Frontiers in Physiology, 2022)
In insects, metamorphosis is controlled by juvenile hormone (JH) and 20-hydroxyecdysone (20E). The Krüppel homolog 1 (Kr-h1), a key JH-early inducible gene, is responsible for the suppression of metamorphosis and the regulation of the Broad-Complex (Br-C) gene, which is induced by 20E and functions as a “pupal specifier”. In this study, we identified and characterized the expression patterns and tissue distribution of DaKr-h1 and DaBr-C at various developmental stages of Dendroctonus armandi. The expression of the two genes was induced by JH analog (JHA) methoprene and 20E, and their functions were investigated by RNA interference. DaKr-h1 and DaBr-C were predominantly expressed in the heads of larvae and were significantly downregulated during the molting stage. In contrast, the DaKr-h1 transcript level was highest in the adult anterior midgut. DaBr-C was mainly expressed in females as adults, with the highest transcript levels in the ovaries. In the larval and pupal stages, both JHA and 20E significantly induced DaKr-h1, but only 20E significantly induced DaBr-C, indicating the importance of hormones in metamorphosis. Precocious DaKr-h1 knockdown in larvae upregulated DaBr-C expression, resulting in precocious metamorphosis from larvae to pupae and the formation of miniature pupae. DaKr-h1 knockdown in pupae suppressed DaBr-C expression, increased emergence, caused abnormal morphology, and caused the formation of small-winged adults. These results suggest that DaKr-h1 is required for the metamorphosis of D. armandi. Our findings provide insight into the roles of DaKr-h1 and DaBr-C in JH-induced transcriptional repression and highlight DaKr-h1 as a potential target for metamorphosis suppression in D. armandi.